2019
DOI: 10.1016/j.compositesa.2019.105478
|View full text |Cite
|
Sign up to set email alerts
|

Influence of friction angle between carbon single fibres and tows: Experimental analysis and analytical model

Abstract: Friction between single fibres or between tows is an important element in the mechanical properties of composite reinforcement. Therefore, knowledge of the friction behaviour at the two scales, tow and fibre, is necessary for a deep understanding of the mechanical behaviour of composite reinforcement. In the models, the strategy used is to consider a constant coefficient of friction. This paper presents an efficient method of measuring the coefficient of friction relative to an inter-tow or inter-fibre sliding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…For carbon fiber tows, the results obtained in Fig. 6 are in line with the literature [42] for similar tows and conditions. As the shear angle increases, the friction coefficient increases as well with a noticeable difference being at 45°(5% increase to initial 0°angle).…”
Section: Effect Of the Angle On The Tow-tow Friction Coefficientsupporting
confidence: 89%
See 1 more Smart Citation
“…For carbon fiber tows, the results obtained in Fig. 6 are in line with the literature [42] for similar tows and conditions. As the shear angle increases, the friction coefficient increases as well with a noticeable difference being at 45°(5% increase to initial 0°angle).…”
Section: Effect Of the Angle On The Tow-tow Friction Coefficientsupporting
confidence: 89%
“…The wear on the other hand decreased the amount of sizing on the tows and as such, the friction coefficient. Then, in another paper, Tourlonias et al [42] investigated the effect of the angle between fibers or tows on the fiber-tofiber and tow-to-tow friction coefficient. they found out that the friction coefficient evolves little except for angles very close to zero, reaching the highest friction coefficient for both configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Similar models of adhesive contact with ideal packing of fibres in a tow were used to explain the experimentally observed dependency of friction on the angle between two carbon tows [9,12,13]. The measured friction coefficient was significantly higher in a parallel arrangement than a perpendicular one, with a very rapid decrease between 0° and 10°, and almost no further change up to 90°.…”
Section: Manuscriptmentioning
confidence: 85%
“…Compared to the individual fibres, the friction of a carbon fibre tow is easier to measure but more difficult to explain and to model. However, there is growing interest in such measurements, as highlighted by recent publications on this topic [5][6][7][8][9][10][11][12][13]. The friction between a carbon tow and a tool was measured by Cornelissen et al [6], using a tow in a contact with a smooth and a rough cylinder, and later by Mulvihill et al, with a smooth [9] and a rough [10] plane; in the latter set of experiments, it was found that the coefficient of friction of a carbon tow was twice as high against a smooth metallic counterface (with an arithmetical mean deviation of the roughness height, Rq = 0.02 µm) than the rough one (Rq = 1.1 µm).…”
Section: Manuscriptmentioning
confidence: 99%
“…The tensile force T 1 of the fiber at different positions can be obtained by applying the Roder method, as follows 30,53…”
Section: Friction and Adhesion Between Fibrous Tows And Spoolsmentioning
confidence: 99%